HBR'S 10 must reads: The definitive management ideas of the year from Harvard Business Review 2019. - Harvard Business School (Harvard Business Review Press, 2019)
This book will make insprise you to: - Make stronger connections and build greater trust among people who work on multiple teams. - Engage customers and employees alike with the help of artificial intelligence. - Channel your outrage about sexual haraament in the workplace into effective action. - Consider how to CEO activism can generate goodwill for your company - and weigh its risks. - Pair data with qualitative research to increase diversity in your organization. - Remain competitive in a hub economy by using your company's assets and capabilities differently